Repeated prolonged moderate-intensity walking exercise does not appear to have harmful effects on inflammatory markers in patients with inflammatory bowel disease. (2nd January 2021) - Lamers, Carlijn R.; de Roos, Nicole M.; Bongers, Coen C. W. G.; ten Haaf, Dominique S. M.; Hartman, Yvonne A. W.; Witteman, Ben J. M.; Hopman, Maria T. E.
Abstract: Background and objectives: The role of exercise in the management of inflammatory bowel disease (IBD) is inconclusive as most research focused on short or low-intensity exercise bouts and subjective outcomes. We assessed the effects of repeated prolonged moderate-intensity exercise on objective inflammatory markers in IBD patients. Methods: In this study, IBD patients (IBD walkers, n = 18), and a control group (non-IBD walkers, n = 19), completed a 30, 40 or 50 km walking exercise on four consecutive days. Blood samples were taken at baseline and every day post-exercise to test for the effect of disease on exercise-induced changes in cytokine concentrations. A second control group of IBD patients who did not take part in the exercise, IBD non-walkers ( n = 19), was used to test for the effect of exercise on faecal calprotectin. Both IBD groups also completed a clinical disease activity questionnaire. Results: Changes in cytokine concentrations were similar for IBD walkers and non-IBD walkers (IL-6 p = .95; IL-8 p = .07; IL-10 p = .40; IL-1β p = .28; TNF-α p = .45), with a temporary significant increase in IL-6 ( p < .001) and IL-10 ( p = .006) from baseline to post-exercise day 1. Faecal calprotectin was not affected by exercise ( p = .48). Clinical disease activity did not change in the IBD walkers with ulcerative colitis ( p = .92), but did increase in the IBD walkers with Crohn's disease ( p = .024). Conclusion: Repeated prolonged moderate-intensity walking exercise led to similar cytokine responses in participants with or without IBD, and it did not affect faecal calprotectin concentrations, suggesting that IBD patients can safely perform this type of exercise.